2004
DOI: 10.3758/bf03194982
|View full text |Cite
|
Sign up to set email alerts
|

Unconscious perception at the objective detection threshold exists

Abstract: Does unconscious perception at the objective detection threshold (ODT) exist? In this reply, formal meta-analyses of previously narratively reviewed evidence (Snodgrass, Bernat, & Shevrin, 2004) provide strong evidence for large, reliable unconscious perceptual effects, and further strengthen previous conclusions for their ODT status. These meta-analyses dispel general concerns that ODT effects are small, unreliable, or susceptible to file drawer concerns (cf. Reingold, 2004). Furthermore, the specific objecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 46 publications
1
17
0
1
Order By: Relevance
“…Subsequent research revealed that at the ODT different things happen than at the supraliminal threshold. For example, in a series of replicated studies (Snodgrass et al, 1993a,b, 2004a,b), Snodgrass discovered inhibitory processes at the ODT that were a function of individual differences, findings quite germane to our current study. These effects were based on standard cognitive tasks (e.g., word choices).…”
Section: Discussionmentioning
confidence: 52%
See 3 more Smart Citations
“…Subsequent research revealed that at the ODT different things happen than at the supraliminal threshold. For example, in a series of replicated studies (Snodgrass et al, 1993a,b, 2004a,b), Snodgrass discovered inhibitory processes at the ODT that were a function of individual differences, findings quite germane to our current study. These effects were based on standard cognitive tasks (e.g., word choices).…”
Section: Discussionmentioning
confidence: 52%
“…For example, mean 1 could be larger than mean 2, but this says nothing about whether scores in condition 1 are correlated with scores in condition 2. We have previously documented in our review (Snodgrass et al, 2004a), extremely subliminal conditions (i.e., wherein detection d ′ = 0) frequently yield exclusively bidirectional effects—that is, effects driven by individual differences but with no main (i.e., mean) effects. This is exactly the case with our data: An ANOVA on our data produced no mean effects, while the regression analysis was strikingly productive.…”
Section: Methodsmentioning
confidence: 81%
See 2 more Smart Citations
“…However, it remained possible that suppression would not be complete on every trial; for instance, some participants might detect letter features on some trials. Debates on the unconscious perception can be found elsewhere in the literature (see Pratte & Rouder, 2009; Snodgrass, Bernat, & Shevrin, 2004; Yang & Blake, 2012). A total of 100 trials were presented: 40 problem word trials, 40 irrelevant word control trials, and 20 catch trials (all catch trials were excluded from the analysis).…”
Section: Methodsmentioning
confidence: 99%